Ultrasmall gold cluster arrays encapsulated in silica nanospheres: applications in fluorescence imaging and catalysis - Samanta, Anupam; Dhar, Basab B.; Devi, R. Nandini (Journal of Physical Chemistry C, 2012)
Facile synthesis of ultrasmall gold nanoclusters of size <2 nm dispersible in water using a novel quaternary ammonium ligand is reported. Further, arrays of these nanoclusters are encapsulated in monodisperse silica nanospheres of size 25-30 nm. The photophysical characteristics of the clusters are found to be intact upon encapsulation, rendering the resulting composite material ideal for fluorescence imaging applications. We have further shown the utilization of these materials in catalysis as precursors for Au nanopartides encapsulated in porous silica.